Perceived Usability Evaluation of Learning Management Systems: Empirical Evaluation of the System Usability Scale - Orfanou, Konstantina; Tselios, Nikolaos; Katsanos, Christos (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
Perceived usability affects greatly student’s learning effectiveness and overall learning experience, and thus is an important requirement of educational software. The System Usability Scale (SUS) is a well-researched and widely used questionnaire for perceived usability evaluation. However, surprisingly few studies have used SUS to evaluate the perceived usability of learning management systems (LMSs). This paper presents an empirical evaluation of the SUS questionnaire in the context of LMSs’ perceived usability evaluation. Eleven studies involving 769 students were conducted, in which participants evaluated the usability of two LMSs (eClass and Moodle) used within courses of their curriculum. It was found that the perceived usability of the evaluated LMSs is at a satisfactory level (mean SUS score 76.27). Analysis of the results also demonstrated the validity and reliability of SUS for LMSs’ evaluation, and that it remains robust even for small sample sizes. Moreover, the following SUS attributes were investigated in the context of LMSs evaluation: gender, age, prior experience with the LMS, Internet self-efficacy, attitude towards the Internet and usage frequency of the LMS.